COMMUNICATION IN THE VILLAGE DISTRICT SELECTION DELIBERATION IN DIMEMBE DISTRICT - Stefanus Ambow; Goinpeace H. Tumbel; Devie S.R. Siwij (Journal of International Islamic Law, Human Right and Public Policy, 2026)
The purpose of this study was to analyze the formal and informal communication patterns between the Village Consultative Body (BPD) and the Village Head (Uku Tua) in the implementation of the Pinilih Village Deliberation (Deliberation), as well as to analyze information transparency, community participation, and decision documentation in inter-institutional communication in the Village Deliberation. The method used was a descriptive qualitative approach with a case study design. Data collection was conducted through in-depth interviews, observation, and document studies, while data analysis followed the Miles and Huberman model. The results showed that formal and informal communication between the BPD and the Village Head (Uku Tua) was not yet balanced; informal communication via WhatsApp, telephone, and in-person meetings was more dominant, but did not leave administrative evidence, making it difficult to evaluate. Information transparency was still hampered by miscommunication on sensitive issues such as Direct Cash Assistance (Bantuan Langsung Tunai). Community participation was not optimal because some residents did not attend without clear reasons. Decision documentation in the form of minutes and minutes was available physically and digitally, but the quality of the content was not strong enough to provide a basis for accountability. Thus, the accountability of the Village Deliberation needs to be supported by a balance of formal and informal communication, greater transparency, equitable participation, and complete and orderly documentation.